PENGALIHAN DANA ZAKAT MENJADI PINJAMAN MODAL USAHA OLEH BAZDA KOTA PADANG DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Zulfan Zulfan (IAIN Padangsidimpuan, 2015)
Abstract: Zakat is one of the pillars Islam which has great potential in poverty reduction, by optimizing the collection and utilization of zakat, infaq, shadaqah in the broadest sense. In the early of Islam, Zakat is one of the funding sources of country and very actively in empowering and building the welfare of the people, especially for economy. In Indonesia, there has been regulation about management zakat is Undang-Undang No 38 Years 1999 about management of zakat. Then, in Some areas, has issued a policy in the local authority to implement the regulation, including the people who manage the zakat. One of the area is the local goverment in Padang has issued a policy to be able to optimaze the potential of zakat in Padang. Optimization of zakat not only in terms of the collection of zakat in a manner required all civil servants in Padang, but also interms of distributions carried out by the local charity mile (BAZDA) Padang. In terms distribution fund zakat which is done by BAZDA Padang, beside that giving zakat without requirements to mustahiq Zakat, there is capital loans to mustahiq zakat who wants open trade .Keyword: Zakat; Amil Zakat; Mustahiq Zakat. Abstrak: Zakat adalah salah satu rukun Islam yang memiliki potensi besar dalam pengurangan kemiskinan, dengan mengoptimalkan pengumpulan dan pendayagunaan zakat, infaq, shadaqah dalam arti yang luas. Pada awal Islam, Zakat merupakan salah satu sumber pendanaan dari negara dan sangat aktif dalam memberdayakan dan membangun kesejahteraan rakyat, terutama bagi perekonomian. Di Indonesia, telah ada peraturan tentang zakat manajemen adalah Undang-Undang No 38 Tahun 1999 tentang pengelolaan zakat. Kemudian, di beberapa daerah, telah mengeluarkan kebijakan di pemerintah daerah untuk melaksanakan peraturan tersebut, termasuk orang-orang yang mengelola zakat. Salah satu daerah adalah pemerintah daerah di Padang telah mengeluarkan kebijakan untuk dapat mengoptimalkan potensi zakat di PadangKata Kunci: Zakat; Amil Zakat; Mustahiq Zakat